(untitled) (Quinto Sol, 2021)
Studies about Peronism at subnational levels as well as research addressing the political violence in the sixties and seventies are consolidated fields in Argentinian historiography. Furthermore, articles on Peronist groups that opposed the sector led by Montoneros have been published in the last fifteen years. In that line of inquiry, various investigations have considered provincial and local settings where intense factional conflicts arose inside the Peronist party. At the intersection of those historiographical questions, this research centers on the case of the Comando de Organización (CO) in the Province of Chaco during the period 1973-1976 and focuses on two conceptual issues. The first one, in line with some key theoretical principles provided by Carl Schmitt’s Theory of the Partisan, poses a description of the type of political violence inflicted by this organization. The second issue refers to the discussion about the use of the term right-wing Peronism to define diverse anti-Montoneros actors. To this end, the ideological propositions of the CO in Chaco are compared with the ideas traditionally held by the Peronist populism.